2014
DOI: 10.1039/c4ta02353f
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for rapid electrolyte wetting in tape cast electrodes for lithium-ion batteries

Abstract: A dramatic acceleration of electrode wetting with liquid electrolyte was achieved by laser-assisted formation of capillary microstructures in cathode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 34 publications
2
124
0
Order By: Relevance
“…37,39,40 In that regard, we investigated the effects of wettability induced by changing the viscosity of the electrolyte. First, in order to confirm the wettability of between the electrolytes on the pressed MWCNT-S electrode, we measured the contact angles.…”
Section: Resultsmentioning
confidence: 99%
“…37,39,40 In that regard, we investigated the effects of wettability induced by changing the viscosity of the electrolyte. First, in order to confirm the wettability of between the electrolytes on the pressed MWCNT-S electrode, we measured the contact angles.…”
Section: Resultsmentioning
confidence: 99%
“…We find that an appropriate structure design and complete removal of the electrode material from the ablation zone delivers the most efficient capillary transport. 11 Nanosecond laser ablation, however, is not appropriate for all 11 Li: Lithium. C: Carbon.…”
Section: Figure 1 Scanning Electron Microscope Images Of Laser-genermentioning
confidence: 99%
“…Therefore, laser direct structuring of the active electrode material has been developed for thin film electrodes made of LiCoO 2 , LiMn 2 O 4 , SnO 2 or fluorine doped SnO 2 (FTO) [14][15][16][17][18][19][20][21][22][23]. In a very recent approach, it was shown that laser-structuring can be applied for LiCoO 2 , LiMn 2 O 4 , LiNi 1/3 Mn 1/3 Co 1/3 O 2 and silicon composite electrodes with film thicknesses of 50 to 100 µm [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%